2015
DOI: 10.1007/s00604-015-1520-x
|View full text |Cite
|
Sign up to set email alerts
|

Screen-printed electrodes modified with carbon nanotubes or graphene for simultaneous determination of melatonin and serotonin

Abstract: Single-walled carbon nanotubes (SWCNT), multiwalled carbon nanotubes (MWCNT) and graphene have been tested as carbon allotropes for the modification of carbon screen-printed electrodes (CSPEs) to simultaneously determine melatonin (MT) and serotonin (5-HT). Two groups of CSPEs, both 4 mm in diameter, were explored: The first includes commercial SWCNT, MWCNT and graphene, the second includes SWCNT, MWCNT, graphene oxide nanoribbons and reduced nanoribbons that were drop casted on the electrodes. The carbon nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…Melatonin capsules 3 mg -additional ingredients soybean oil, glycerol, beeswax, soybean lecithin -(Melatonina, Bio-Synergie Activ S.R.L., France) were purchased from a local pharmacy. To avoid analyte degradation, the extraction of ML was done under dark conditions [36,43]. The liquid of the capsules was diluted with 3 mL of methanol according to the method of Gomez, et al [43], then vortexed for 40 s and sonicated in an ultrasound bath for 10 min.…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin capsules 3 mg -additional ingredients soybean oil, glycerol, beeswax, soybean lecithin -(Melatonina, Bio-Synergie Activ S.R.L., France) were purchased from a local pharmacy. To avoid analyte degradation, the extraction of ML was done under dark conditions [36,43]. The liquid of the capsules was diluted with 3 mL of methanol according to the method of Gomez, et al [43], then vortexed for 40 s and sonicated in an ultrasound bath for 10 min.…”
Section: Sample Preparationmentioning
confidence: 99%
“…In the latest years melatonin has also been detected by using electrochemical detection [33][34][35][36]. Electrochemical methods offer advantages including acceptable sensitivity, low cost of instrument, wide linear concentration range, possibility of miniaturization.…”
mentioning
confidence: 99%
“…The highest sensitivity for the simultaneous determination of 5-HT and MT was obtained from graphene oxide nanoribbon-based electrode at the potentials of 0.05 V for 5-HT and 0.39 V for MT (vs. Ag) in DPV measurements, respectively. They found that carbon nanomaterial-modified electrode can be used as an excellent platform for simultaneous sensing in even small sample volumes [ 114 ].
Scheme 8 a Fabrication of the hierarchical FeN NPs/NG core–shell.
…”
Section: Graphene-based Biosensorsmentioning
confidence: 99%
“…The pioneering work by Adams [17] and Wightman [18] and the resulting fast response times and low detection limits allowed development of electroanalytical approaches which complement conventional chromatographic/spectroscopic methods [19][20][21][22][23]. In this context, Gomez et al reported a sensor based on single-walled carbon nanotubes (SWCNT), multi-walled carbon nanotubes (MWCNT) and graphene for 5-HT and melatonin detection [24]. Recently, Sharma et al compiled a review article regarding chemically modified electrodes for serotonin detection [25] and Makrlíková et al have Electronic supplementary material The online version of this article (https://doi.org/10.1007/s00604-018-2949-5) contains supplementary material, which is available to authorized users.…”
mentioning
confidence: 99%
“…performanceGomez FJV et al[24] Carbon nanotubes and graphene modified carbon screen-printed electrodes (CSPEs) Differential pulse voltammetry MT (melatonin) Detection limit: 1.1 and 5-HT Detection limit 0.Gu Ran et al[23] Multiwalled carbon nanotubes, chitosan and poly(p-aminobenzenesulfonic) modified glassy carbon electrode Differential pulse voltammetry 5-HT Linear range: 0.10.1 mM Detection limit: 80 nM.Goyal et al[8] . Anithaaa and al [35].…”
mentioning
confidence: 99%